Comparison of testicular stiffness values obtained by ultrasound shear-wave elastography and magnetic resonance elastography in normal healthy volunteers - Poçan, Süheyl; Karakaş, Levent (The European Research Journal, 2024)
Objectives: This study aimed to contribute to the standardization of elastography by comparing stiffness values obtained from ultrasound shear wave elastography (SWE) and magnetic resonance elastography (MRE) of the testicular parenchyma in healthy volunteers. Methods: A total of 22 healthy volunteers (44 testes) were included in this study. Of the 26 cases analyzed, four were excluded from the study due to the exclusion criteria. The testicular parenchyma of the included patients was evaluated using MRE and SWE examinations. Pearson’s correlation test was used to calculate the correlation between age and stiffness values, testicular volumes and stiffness values, and stiffness values from both examinations. Results: The mean SWE stiffness of the right testes was 5.560±3.1 kPa and the mean SWE stiffness of the left testes was 5.361±2.9 kPa. The mean MRE stiffness of the right testes was 6960.11±460 Pa and the mean MRE stiffness of the left testes was 6560.19±310 Pa. There was no significant correlation between SWE and MRE stiffness values (P=0.096). There was also no significant statistical correlation between SWE and MRE stiffness values and testicular volumes (P=0.17 and P=0.093, respectively). Conclusions: No statistical correlation was found between the stiffness values obtained by SWE and those obtained by MRE in the normal testicular parenchyma. Additionally, no conclusive relationship between stiffness levels, age, or testicular volume was discovered.